Efektivitas Konseling Kelompok Menggunakan Teknik Sosiodrama untuk Meningkatkan Kepercayaan Diri Siswa di SMP Negeri 18 Pontianak - Restini, Anjellina; Yuline, Yuline; Amallia Putri (Edu Berkah Khatulistiwa, 2024)
The purpose of this study is to evaluate the impact of group counselling at SMP Negeri 18 Pontianak that use sociodrama techniques to boost students' self-confidence. The study methodology is quantitative-experimental, utilising a one-group pre-test and post-test design with a pre-experimental design. Six students with poor self-confidence were included in the study's sample, which was drawn from the 67 students in classes VIII C and D. These students' questionnaire findings were analysed. Purposive sampling, a Non-Probability sampling approach, was employed in the sampling process. Calculations revealed that, on average, students' levels of self-confidence were 57 before receiving therapy (Pre-test) and 97 after receiving treatment (Post-test). The Paired Sample T-Test was used for statistical testing, and the results showed that there was a significant difference in the level of student self-confidence before and after receiving group counselling using sociodrama techniques. The T count was -9.530 with a sig value of 2 (Tailed) 0.000 < 0.05, meaning Ha is accepted and Ho is rejected. Thus, it was determined that group counselling at SMP Negeri 18 Pontianak employing sociodrama approaches was successful in raising students' self-confidence.